Determinants of Shea Nut Marketing Arrangements in Northern Uganda. - Akatwetaba, Deborah; Okello Daniel, Micheal; Kasharu, Apollo; Egeru, Anthony; Mugonola, Basil (Kabale University, 2024)
This study assessed factors influencing shea nut actors’ choices of shea nut marketing arrangements in northern Uganda. An understanding of these factors is vital in influencing the choice of the different marketing arrangements. Cross-sectional data was collected from a sample of 325 shea nut actors. Data was analyzed using descriptive statistics and a multinomial logit model. The shea nut actors in this study were composed of 78% collectors, 16% traders, and 7% processors. About 73% and 43% of shea collectors and traders, respectively, sold their shea nuts and/or products through spot markets, while, 45% of the processors sold their shea nuts and/or products through informal contracts. A formal contract was the least common marketing arrangement among all the actors. The probability of choosing each marketing arrangement was influenced by several factors including experience, education, income level, access to extension, training, access to credit, awareness of innovations in the shea value chain, awareness of value addition supporting institutions, main occupation (farming), distance to the market, access to information and means of transport used (head portage). Efforts to increase formal contract participation should focus on providing extensions and creating awareness about institutions that support value addition. There is a need for a location and actor-specific approach in promoting the different market arrangements in shea products marketing.